Adaptive capacity of Dwarf Chameleon (Bradypodion) thermoregulation in a changing environment - Ebrahim, Azraa (My University, 2023)
We are currently undergoing a period of rapid climate change and habitat transformation resulting from growing urbanisation. Species with low dispersal abilities cannot track suitable climate and must adapt to the new environmental conditions if they are to persist. Studying how species have responded to past and ongoing climatic changes can provide insight on their potential adaptive capacity and may be used to predict future responses to similar changes. The overall aim of this study was to assess the adaptive capacity of Dwarf Chameleon (Bradypodion) thermal biology on two timescales. Firstly, I compared the vertical thermal profiles between the sites of three forest species (B. damaranum, B. setaroi, and B. thamnobates) and two fynbos/grassland (B. barbatulum and B. melanocephalum) species. Environmental temperatures were measured using arrays of iButtons set up at 1-m intervals for a 10 m vertical profile. For the grassland/fynbos habitats, an additional array of iButtons was set up at 0.2-m intervals for a 1 m vertical profile. The hypothesis was that forest habitats would have more moderate temperatures (5 – 35 °C) than grasslands or fynbos, and that forests would have a distinct thermocline from the ground up. As a result, I hypothesised that forest species would have different selected temperatures (Tsel ) to fynbos and grassland species. To measure Tsel , chameleons were placed in a thermal gradient and body temperatures were measured in one-hour intervals for a six-hour period. Environmental temperatures for B. barbatulum and B. setaroi were similar. All the other sites had differences in their thermal profiles at each height interval. Tsel was also similar for B. barbatulum and B. setaroi, as well as B. damaranum and B. thamnobates. T sel differed between all other species. Secondly, adaptive capacity over a short time scale was evaluated by comparing environmental temperatures and chameleon Tsel in natural and urban sites for four species of Bradypodion. For all species, there were environmental temperature differences between natural and urban sites. Only B. thamnobates showed a difference in Tsel between sites. Overall, the results from the study suggest that there is some adaptive capacity of the thermal biology of Bradypodion. While behaviour can often mitigate the effects of environmental changes, it may become too costly where these differences are too great, and species may undergo physiological adaptation.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Animal, Plant, and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2022